Manifestações orais e sistêmicas em paciente portador de imunodeficiência primária submetido a tratamento com imunoglobulina: relato de caso - Klein, Amanda Gomes (2020)
Hypogammaglobulinemia is an alteration in humoral immunity, characterized by low serum levels of antibodies, which can have primary and secondary causes. As a result, patients with hypogammaglobulinemia are susceptible to recurrent or chronic bacterial infections. Oral manifestations related to primary immunodeficiency are rarely reported in the literature. A few studies suggest a higher prevalence of lichenoid lesions, periodontal diseases, pseudomembranous candidiasis, recurrent aphthous ulcer (UAR) and enamel hypoplasia. This study aims to contribute to knowledge in order to assist the dentist in the early detection of oral manifestations, such as their possible changes and complications, associated with primary immunodeficiencies, specifically hypogammaglobulinemia. This is a case study, carried out by means of documentary analysis of medical-dental records and clinical assessment intra and extraoral, in a 19-year-old patient, in a male patient, feoderma accompanied at the Hospital da Criança in Brasília José Alencar, presenting a picture of primary immunodeficiency and comorbidities, in order to detect the prevalence of oral manifestations in patients affected by hypogammaglobulinemia.